MEMBANGUN MORALITAS DALAM ARUS POSTMODERNISME - Nadeak, Largus (UNIKA Santo Thomas, 2005)
A strong current in thinking nowadays is postmodernism. It is signed by the changes of opinion and by calling in question the absoluteness of reason, and tradition. We should observe the sign of our times, and afterward we ask what we should do. We answer our question by reconstructing morality with some important ideas as follows: 1) We refound our morality on truth known by faith and reason; 2) To make moral as a critical instrument in searching goodness; 3) To restore our moral habit by knowing virtues (back to virtues).